Utilization of Dato Karama's Biography as a History Learning Resource to Improve the Understanding of Local History of Grade X Students at SMA Negeri 4 Sigi - Ilma Wandini Mills (Journal of Education and Teaching Learning, 2026)
Learning history in school is often associated with negativity, as an uninteresting subject based on abstract text-book national knowledge. This research intended to conduct an investigation on the use of biography books of Dato Karama as a local history learning source, and to examine the rise in the level of understanding of history among students. The type of research conducted was descriptive qualitative research. It used one history teacher and 153 students as research subjects. Data were gathered through structured interview, classroom observation, pre-test and post-test instrument, which were then analyzed using the interactive model. The result showed that incorporating the biography into PBL syntax increased students' interest significantly. In term of numbers, the students' cumulative average percentage of local history understanding increased significantly from 46.6% before the test to 80.6% after the test. In conclusion, using the local biography is very effective in increasing students' contextual understanding of history and moral exemplary value of local figures.